PROSES PEMBELAJARAN DALAM SETTING INKLUSI DI SEKOLAH DASAR - Rona - Fitria (Universitas Negeri Padang, 2012)
This study originated from the merger of studying children with normal children with special needs in regular schools. Children with special needs are usually placed at the Extraordinary School can now attend regular schools in inclusive education system. To see the implementation of inclusive education, conducted research studies are descriptive kualitatif.Subjek classroom teacher and guidance counselor khusus.Hasil inclusion setting research that learning done quite well, but the obstacles teachers have used varying methods and lack of cooperation with the classroom teacher tutor special.